Rectifier Antenna Design for Wireless Sensor Networks - Tudose, Dan Stefan; Voinescu, Andrei (2013 19th International Conference on Control Systems and Computer Science, 2013)
Wireless Sensor Networks (WSNs) is a technology which is increasingly implemented in a multitude of data acquisition, data processing, and control applications. A rectifier antenna, or rectenna is a device used to convert radio frequency energy into electrical energy through the use of a rectifier circuit attached directly to a regular antenna. For most purposes, rectennas are used for microwave energy transmission, due to their high efficiency in converting microwaves into electrical energy. In this paper, we study the efficiency of rectifier antennas in harvesting energy and their applicability for powering Wireless Sensor Nodes.